Cation effect on ionic liquid-involved polymer electrolytes for solid-state lithium metal batteries. (17th May 2022) - Lin, Xiujing; Liu, Xinshuang; Xu, Shiyuan; Liu, Zeyu; Zhao, Cuie; Liu, Ruiqing; Li, Pan; Feng, Xiaomiao; Ma, Yanwen
Abstract : The effect of ionic liquids with varied cations on the electrochemical performance of Li/LiFePO4 batteries is investigated in terms of cationic solvation. Abstract : Solid polymer electrolytes (SPEs) for lithium metal batteries (LMBs) exhibit predominant safety over traditional carbonate-based organic liquid electrolytes. However, the low ionic conductivity of SPEs related to crystallinity at room temperature still hinders their practical application. The incorporation of nonflammable and ion-conductive ionic liquids (ILs) as plasticizer agents plays an active role in suppressing crystallinity. Herein, the relationship between the cations for ILs and the cycling performance of Li/LiFePO4 batteries were investigated. EMIM + demonstrates the best ability for reversible Li + intercalation/deintercalation behavior over other cations due to its superior cationic solvation, highest ion conductivity and lowest viscosity. The Li/LiFePO4 batteries based on the optimized EMIM + -encapsuled ionogel electrolyte could operate steadily over 120 cycles at 0.5C and room temperature. The results illustrate that the IL-plasticized hybrid electrolyte is a promising electrolyte candidate for room temperature solid state LMBs with high energy densities.